The Effects of Frying Time and Temperatures on Fatty Acids Profile of Blanched Potato Chips - Nizori, Addion; Mishra, Vijay (Indonesian Food Science and Technology Journal, 2018)
The aim of this research was to study whether the frying time and temperature affected fatty acids profiles of blanched potato chips. Factorial designs were carried out using a completely randomized design (CRD) two factor (time and temperature) and three levels with two replications. Frying temperature was set up at 160 0C, 180 0C and 200 0C. The potato chips were fried for 3, 5, 7 minutes. The oil type used was sunflower. The fatty acids profiles were analyses with capillary gas liquid chromatography (Varian 3400) equipped with an auto sampler and a flame ionization detector (FID) using a 50 m x 0.32 mm (I.D) fused silica bonded phase capillary column (BPX70, SGE, Melbourne, Australia). The experiments were run in duplicate and the present results are the average of the obtained values. ANOVA analysis of the results was carried out using SPSS software (version 11, 2004). The key plot software for making three dimensions was the sigma plot scientific graphing software. The results showed moisture content and colour index of blanched potato chips decreased significantly with increasing frying time and temperature. Furthermore, unsaturated fatty acids (cis oleic and linoleic) decrease after long period frying.